„Tu wszystko ma insze imię”, czyli o zmianach semantycznych w polszczyźnie potomków polskich imigrantów w Brazylii - Goczyła Ferreira, Alicja (Słowo. Studia językoznawcze, 2020)
The object of this research are lexical semantic changes in Polish language spoken by descendants of Polish immigrants who live in a rural community in southern Brazil. The aim is to analyze the semantic changes which emerged as a result of language contact with Brazilian Portuguese and to state if there is a semantical motivation between the primary meaning (brought by the immigrants) and the new meaning of the lexemes. The data used for the research was extracted from interviews conducted with nineteen Polish descendants. In the data there were found 64 lexemes which underwent a contact-induced semantic change. In 83% of cases there is a semantic link between the primary and the new meaning, which proves that the contact-induced semantic change can be subject to similar mechanisms that result in semantic change within one language only. The mechanisms observed most frequently in the data are generalization and metaphorization.